Preparation, Optimization, Characterization, and Evaluation of Rosuvastatin Loaded Solid Lipid Nanoparticles Using Quality by Design Approach: Pharmaceuitcal Science-Pharmaceutics - B Chaudhari, Nilesh; G Zalte, Amar; S Gulecha, Vishal (International Journal of Life Science and Pharma Research, 2023)
The present research work aims to prepare and characterize solid lipid nanoparticles (SLN) containing rosuvastatin calcium (RT). We aim to use a novel microwave-assisted microemulsion technique to produce Rosuvastatin-loaded SLN. The characterization of the optimized formulation of RTSLN was carried out by employing Fourier-transformed infrared spectroscopy (FTIR) and Differential scanning calorimetry (DSC) studies showed that there was no chemical interaction between drug (Rosuvastatin Calcium) and lipid (GMS), XRD indicated the amorphization of RTSLN formulation. In contrast, scanning electron microscopy (SEM) studies indicated that Rosuvastatin Calcium loaded SLNs are spherical, discrete, and homogeneous. In vitro and ex vivo drug release studies showed sustained drug release action. The effect of dependent variables such as entrapment efficiency (EE), particle size, and independent variables like % GMS and Poloxamer 407 was observed using a 32-factorial design approach. Optimized formulation was selected based on the 2D & 3D counter and surface response plots. The prepared formulations show percentage entrapment efficiency within the range of 53 to 78%, particle size in the 254.2 to 863.4 nm, and in vitro drug release was found to be 79.8%. Also, ex vivo absorption was 76.7 % for 8 hours. The need of the research work is to use microwave energy over conventional heating to prepare SLNs also helps to resolve problems associated with conventional colloidal drug delivery systems, which leads to improved drug bioavailability.